Evolutionary Mechanism of Immunological Cross-Reactivity Between Different GII.17 Variants - Zuo, Yueting; Xue, Liang; Gao, Junshan; Liao, Yingyin; Liang, Yanhui; Jiang, Yueting; Cai, Weicheng; Qin, Zhiwei; Yang, Jiale; Zhang, Jumei; Wang, Juan; Chen, Moutong; et al. (Frontiers in Microbiology, 2021)
Human norovirus is regarded as the leading cause of epidemic acute gastroenteritis, with GII.4 being the predominant genotype during the past decades. In the winter of 2014/2015, the GII.17 Kawasaki 2014 emerged as the predominant genotype, surpassing GII.4 in several East Asian countries. Hence, the influence of host immunity response on the continuous evolution of different GII.17 variants needs to be studied in depth. Here, we systematically studied the evolutionary mechanism of four clusters of GII.17 strains (clusters A-D) by investigating the cross-reactivity and cross-protection of their respective antisera. Antisera of previous strains of GII.17 A and GII.17 B cross-reacted with recent variants GII.17 C and GII.17 D, showing high OD values ranging from 0.8 to 1.16, while the OD values of recent variant antisera cross-reacting with previous strains were weak, ranging from 0.26 to 0.56. The cross-protection assay indicated that the antisera of previous strains had no inhibitory effect on recent variants. Finally, mutations at amino acids 353-363, 373-384, 394-404 and 444-454 had the greatest impact on cross-reactivity. These data indicate that recent pandemic variants GII.17 C and GII.17 D avoided the herd immunity effect of previous GII.17 A and GII.17 B strains through antigenic variation.